Tulehduksen ja suolistomikrobiston merkitys paksusuolensyövän puoleisuuserossa - Lainio, Jenni (2024)
Colorectal cancer is the third most common cancer in the world. It is considered a lifestyle disease. Colorectal cancer is divided into right-sided and left-sided cancer tumours depending on their location in the colon. Most tumours are left-sided, but the right-sided ones have a worse prognosis. Side differences include gut microbiota and inflammation levels. Right-sided tumours have a higher inflammation rate and they have been shown to contain more bacteria-related biofilms. It has been demonstrated that biofilm increases cytokines Interleukin-6 and CCL2/MCP-1 in the tumour microenvironment, which are the most common cause of inflammation in colorectal cancer. The reasons for tumour sidedness are largely unclear, which is why the effects of sidedness on microbiota and inflammatory factors in colorectal cancer were studied in this thesis. The samples and data were collected from eight colorectal cancer patients who were operated on in the Central Finland Health Care District. They were voluntarily recruited to SUOPA research of which this MSc thesis is part. From stool and tumour samples the microbiota was analysed by sequencing the bacterial 16S rRNA gene. The gene expression of cytokines and Toll-like receptor 5 from tumour samples was defined by quantitative real-time PCR. Statistical analyses of gene expression were done with the SPSS program and statistical analyses of the microbiota with the CLC Microbial Genomics program. The small sample size proved to be challenging, not providing significance in gene expression. However, statistical significance was observed in one bacterial order, Clostridiales (p=0,02), and in five bacterial genera including Family XIII AD3011 group (p=0,05), Roseburia (p=0,02), Ruminiclostridium 9 (p=0,03), four Asteroleplasma (p=0,02; p=0,03; p=0,04 & p=0,05) and two Christensenellaceae R-7 group (p=0,03 & p=0,04) of OTUs. Most of these belong to Firmicutes, which is known to be elevated in patients with colorectal cancer. All the bacteria have been associated with increasing levels in left-sided tumour patients, but the role of some of them in gut and colorectal cancer is not well studied. As the material was small, bigger sample sizes should be studied in the future.